Simulasi Teks Berjalan pada LCD I2C Berbasis Arduino Uno Menggunakan Simulator Online sebagai Media Prototipe Virtual - M. Asep Rizkiawan; Zeluyvenca Avista; Eko Kurniawan; Baharuddin Ghalib (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The rapid development of microcontroller technology has driven innovations in digital display systems, including the use of I2C-based LCD modules for efficient communication. However, limited access to physical hardware remains a challenge for students and novice researchers. This study proposes an online simulation model for implementing a running text system using a 16×2 I2C LCD controlled by an Arduino Uno on the Wokwi platform. The method follows a digital system engineering approach, including system design, Arduino-based programming (C++), and virtual testing. The results show that the system successfully displays scrolling text with stable performance, achieving an average delay of 200–300 ms per character shift and consistent operation without simulation errors. Memory usage remains below 60% of available capacity, indicating efficient resource utilization. Compared to previous studies that primarily use LCDs as supporting components, this work focuses on the running text module as the main system, contributing a structured simulation model for educational and prototyping purposes. These findings demonstrate that Wokwi provides an effective, low-cost, and accessible platform for early-stage development and validation of microcontroller-based display systems.